Desenvolvimento de filme polimérico à base de hemicelulose extraída do bagaço de cana-de-açúcar - Braga, Roberta da Silva (My University, 2018)
The use of agricultural residues as a renewable biomass source, capable of producing new less polluting compounds, is increasing. Sugarcane bagasse, an abundant residue of the sugar-alcohol industry, usually destined to incineration for energy generation, presents a great potential to be exploited as source biomass of polysaccharides. Sugarcane bagasse is composed of 25 to 30% hemicellulose, a heteropolysaccharide with a high molar mass, which can be used in several applications, such as in the food, biomedical, cosmetic, textile and paper industries, especially as a stabilizer emulsifiers, viscosifying agent, gelling agent, film and soluble dietary fiber. The objective of this study was to develop polymeric films based on hemicellulose extracted from sugarcane bagasse, to characterize the extract and to evaluate the properties of the formulated films using concentrations of 2%, 3% and 4% (m / v) of hemicellulose. One hundred grams of bagasse was extracted with ethanol 95% (v /v), followed by hydrolysis with 2,5 L of 0,5 M NaOH. Three volumes of ethanol 95% were used to precipitate the hemicellulosic content, subsequently separated by centrifugation and dried at room temperature for 24 hours, for further characterization by FTIR. The films were produced by the casting method, which consists of the dispersion of the film-forming solutions, prepared in different concentrations of hemicellulose, on a polymer surface and dried at room temperature. Mechanical, thermal, morphological and physical properties, such as thickness and solubility, of the films were investigated. In the FTIR spectra was observed characteristic bands of bonds present in hemicellulosic compounds. The films, with different concentrations of hemicellulose, present average thicknesses ranging from 0,0316 to 0,0401 mm and water solubility percentages from 85,6% to 92,7%. The degradation and thermal stability profiles for the films studied at different hemicellulose concentrations were similar to each other, with the highest residue at 800 °C obtained for the 3% (w/v) film. It was observed that the increase in the hemicellulose concentration in the films causes an increase in the tensile strength, and the film containing 4% (m/v) was the most resistant among those studied (23,64 ± 2,25 MPa). Morphologically, the films presented a compact and dense structure. This study demonstrated the potential use of sugarcane bagasse in the development of polymer films (sic).
É crescente a utilização de resíduos agrícolas como fonte renovável de biomassa, capazes de originar novos produtos menos poluentes. O bagaço da cana-de-açúcar, resíduo abundante da indústria sucro-alcooleira, normalmente destinado a incineração para geração de energia, apresenta um grande potencial a ser explorado como biomassa fonte de polissacarídeos. O bagaço da cana-de-açúcar é composto de 25 a 30% por hemicelulose, heteropolissacarídeo de elevada massa molar, que pode ser utilizado em diversas aplicações, como na indústria alimentícia, biomédica, cosméticas, têxtil e de papel, especialmente como estabilizante de emulsões, agente viscosificante, gelificante, filme e fibra dietética solúvel. O objetivo desse estudo foi desenvolver filmes poliméricos à base de hemicelulose extraída do bagaço de cana-de-açúcar, caracterizar o extrato obtido e avaliar as propriedades dos filmes formulados utilizando concentrações de 2%, 3% e 4% (m/v) de hemicelulose. Uma alíquota do bagaço foi primeiramente extraído com etanol, seguido de hidrólise alcalina utilizando hidróxido de sódio. Três volumes de etanol 95% foram utilizados para precipitar o conteúdo hemicelulósico, posteriormente separado por centrifugação e secagem, para posterior caracterização por FTIR. Os filmes foram produzidos, a partir do método casting, que consiste na dispersão das soluções filmogênicas, preparadas em diferentes concentrações de hemicelulose, em uma superfície polimérica e secas a temperatura ambiente. Propriedades mecânicas, térmicas, morfológicas e físicas, tais como espessura e solubilidade, dos filmes foram investigadas. Nos espectros de FTIR foram observadas bandas características das ligações presentes em compostos hemicelulósicos. Os filmes, em diferentes concentrações de hemicelulose apresentaram espessuras médias variando de entre 0,0316 e 0,0401 mm e percentuais de solubilidade em água para os filmes de 85,6% a 92,7%. Os perfis de degradação e estabilidade térmica para os filmes estudados em diferentes concentrações de hemicelulose se mostraram semelhantes entre si, sendo o maior teor de cinzas à 800°C obtido para o filme de 3%(m/v). Observou-se que o aumento na concentração de hemicelulose nos filmes ocasiona um aumento na resistência a tração, sendo que o filme contendo 4% (m/v) se mostrou o mais resistente dentre os estudados (23,64 ± 2,25 MPa). Morfologicamente, os filmes apresentaram uma estrutura compacta e densa. Este estudo demonstrou a potencial utilização do bagaço de cana-de-açúcar no desenvolvimento de filmes poliméricos (sic).
Keywords: Hemicelulose; Bagaço de cana